Energy intake variability in free-living young children. Issue 11 (2nd May 2008) - Nielsen, S B; Montgomery, C; Kelly, L A; Jackson, D M; Reilly, J J
Abstract : It has been suggested that young children regulate their daily energy intake very closely with highly stable day-to-day total energy intake. This hypothesis was developed on the basis of an experimental study of 15 children aged 26 to 62 months, which reported a within-subject coefficient of variation (CV) in daily energy intake of 10.4%. We tested the hypothesis that free-living energy intakes were highly stable on a day-to-day basis in a sample of free-living young children from Glasgow, Scotland. In 101 children (47 boys) aged 2.6–6.8 years, energy intake was measured using multiple-pass 24-h recalls. Within-subject CV was 19.2%, which was significantly higher than the 10.4% reported by previously Birch and colleagues ( p <0.0001). In addition, we identified four other studies on free-living children with within-subject CVs ranging from 16.1–28.7%. This evidence indicates that young children show a wide intra-individual variation in day-to-day regulation of energy intake in a free-living environment.